OsMADS26 Negatively Regulates Resistance to Pathogens and Drought Tolerance in Rice . Issue 4 (30th September 2015) - Khong, Giang Ngan; Pati, Pratap Kumar; Richaud, Frédérique; Parizot, Boris; Bidzinski, Przemyslaw; Mai, Chung Duc; Bès, Martine; Bourrié, Isabelle; Meynard, Donaldo; Beeckman, Tom; Selvaraj, Michael Gomez; Manabu, Ishitani; et al.
Abstract : A MADS-box transcription factor represses resistance to pathogenic microorganisms and water deficit, and its down-regulation results in improved biotic and abiotic stress tolerance of rice. Abstract: Functional analyses of MADS-box transcription factors in plants have unraveled their role in major developmental programs (e.g. flowering and floral organ identity) as well as stress-related developmental processes, such as abscission, fruit ripening, and senescence. Overexpression of the rice ( Oryza sativa ) MADS26 gene in rice has revealed a possible function related to stress response. Here, we show that OsMADS26 -down-regulated plants exhibit enhanced resistance against two major rice pathogens: Magnaporthe oryzae and Xanthomonas oryzae . Despite this enhanced resistance to biotic stresses, OsMADS26 -down-regulated plants also displayed enhanced tolerance to water deficit. These phenotypes were observed in both controlled and field conditions. Interestingly, alteration of OsMADS26 expression does not have a strong impact on plant development. Gene expression profiling revealed that a majority of genes misregulated in overexpresser and down-regulated OsMADS26 lines compared with control plants are associated to biotic or abiotic stress response. Altogether, our data indicate that OsMADS26 acts as an upstream regulator of stress-associated genes and thereby, a hub to modulate the response to various stresses in the rice plant.